Epidural Catheter Breakage In-Situ - Geetanjali S Verma (The Indian Anaesthetists' Forum, 2014)
A 45yr old woman diagnosed with dysfunctional uterine bleeding and incisional hernia was planned for total abdominal hysterectomy with bilateral salpingo-oophorectomy and mesh repair under combined spinal and epidural anaesthesia. Using VYGON® epidural catheter with its recommended introducer, the catheter was inserted but it snapped off at 11cm mark while positioning the catheter. After radiological confirmation, the neurosurgeon removed the catheter under general anaesthesia, which was followed by the scheduled surgery.